Foxo3 Knockdown Mediates Decline of Myod1 and Myog Reducing Myoblast Conversion to Myotubes - Benjamin Gellhaus; Kai O. Böker; Marlene Gsaenger; Eyck Rodenwaldt; Marc A. Hüser; Arndt F. Schilling; Dominik Saul (Cells, 2023)
Sarcopenia has a high prevalence among the aging population. Sarcopenia is of tremendous socioeconomic importance because it can lead to falls and hospitalization, subsequently increasing healthcare costs while limiting quality of life. In sarcopenic muscle fibers, the E3 ubiquitin ligase F-Box Protein 32 (Fbxo32) is expressed at substantially higher levels, driving ubiquitin-proteasomal muscle protein degradation. As one of the key regulators of muscular equilibrium, the transcription factor Forkhead Box O3 (FOXO3) can increase the expression of Fbxo32, making it a possible target for the regulation of this detrimental pathway. To test this hypothesis, murine C2C12 myoblasts were transduced with AAVs carrying a plasmid for four specific siRNAs against Foxo3. Successfully transduced myoblasts were selected via FACS cell sorting to establish single clone cell lines. Sorted myoblasts were further differentiated into myotubes and stained for myosin heavy chain (MHC) by immunofluorescence. The resulting area was calculated. Myotube contractions were induced by electrical stimulation and quantified. We found an increased Foxo3 expression in satellite cells in human skeletal muscle and an age-related increase in Foxo3 expression in older mice in silico. We established an in vitro AAV-mediated FOXO3 knockdown on protein level. Surprisingly, the myotubes with FOXO3 knockdown displayed a smaller myotube size and a lower number of nuclei per myotube compared to the control myotubes (AAV-transduced with a functionless control plasmid). During differentiation, a lower level of FOXO3 reduced the expression Fbxo32 within the first three days. Moreover, the expression of Myod1 and Myog via ATM and Tp53 was reduced. Functionally, the Foxo3 knockdown myotubes showed a higher contraction duration and time to peak. Early Foxo3 knockdown seems to terminate the initiation of differentiation due to lack of Myod1 expression, and mediates the inhibition of Myog. Subsequently, the myotube size is reduced and the excitability to electrical stimulation is altered.